Niche partitioning between coexisting gentoo Pygoscelis papua and Magellanic penguins Spheniscus magellanicus at Martillo Island, Argentina - Harris, Sabrina; Scioscia, Gabriela; Klemens, Pütz; Thomas, Mattern; Raya Rey, Andrea Nélida (Marine Biology)
Marine top predators living in sympatry tend to use their environment differentially, thereby reducing niche overlap. Magellanic penguins (Spheniscus magellanicus) and gentoo penguins (Pygoscelis papua) coexist at Martillo Is., Argentina. During the 2014, 2015 and 2017 breeding seasons a total of thirty-one Magellanic and eleven gentoo penguins were equipped with GPS-TDR loggers to record foraging trips. Both species dove to similar maximum depths with analogous effort (dives per hour). Magellanics, however, undertook longer trips and travelled further away from the colony (25 h and 43 km vs. 10 h and 20 km on average, respectively). Gentoos on the other hand, performed longer dives, had a higher percentage of “U” shaped dives and spent more time during the bottom phase of the dive. Gentoos foraged exclusively within an area close to the colony and in waters not deeper than 80 m. Magellanics had more variability in their behaviors and were not associated to a specific depth or distance from the colony. The ecological circumstances of both species (targeted prey and surrounding environment) suffice to explain the particular behaviors of both species independently from the presence of the other. Gentoos seem to focus on benthic prey which remains stable in this environment throughout the year, and Magellanics behave more opportunistically searching for pelagic prey during early chick rearing. Competition may not be always shaping coexistence of species of similar trophic positions and behaviors. Particularly, if resources are not limited, both species can behave in ways they find optimal without factoring the coexistence of the other species. Fil: Harris, Sabrina. Wildlife Conservation Society; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Scioscia, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Klemens, Pütz. Antarctic Research Trust; ...